2019
DOI: 10.1039/c9ra02327e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxidant species on direct, non-syngas conversion of methane to methanol over an FePO4 catalyst material

Abstract: The effect of the phase transformation of a FePO4 catalyst material from the tridymite-like (tdm) FePO4 to the α-domain (α-Fe3(P2O7)2) during the direct selective oxidation of methane to methanol was studied using oxidant species O2, H2O and N2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The lattice oxygen is not relevant to the formation of formaldehyde, as the products are only CO and CO 2 , similar to the Mo-based catalyst. Furthermore, metal phosphates have received considerable attention [128,[130][131][132][133], and optimized catalyst design and process modifications may enable these metal salts to becoming promising alternatives to metal oxide catalysts.…”
Section: Iron-based Catalystmentioning
confidence: 99%
“…The lattice oxygen is not relevant to the formation of formaldehyde, as the products are only CO and CO 2 , similar to the Mo-based catalyst. Furthermore, metal phosphates have received considerable attention [128,[130][131][132][133], and optimized catalyst design and process modifications may enable these metal salts to becoming promising alternatives to metal oxide catalysts.…”
Section: Iron-based Catalystmentioning
confidence: 99%
“…3,5 Hence, the activation and transformation of CH 4 usually require extremely harsh reaction conditions. [6][7][8] A series of technologies have been developed to convert CH 4 into higher-value molecules, including the traditional steam/dry reforming, oxidative/non-oxidative coupling and partial oxidation of CH 4 9-11 and recently developed thermos-photo hybrid processes. [12][13][14] Among the various approaches, partial oxidation of CH 4 into methanol (CH 3 OH) and other oxygenates is one of the most appealing routes for the effective utilization of the natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…However, CH 4 is the most robust organic molecule with perfectly symmetrical tetrahedral structure, high CH bond energy (438.8 kJ/mol), 2 high ionization potential (12.5 eV), 3 low proton affinity (4.4 eV), 4 and weak acidity ( pK a = 48) 3,5 . Hence, the activation and transformation of CH 4 usually require extremely harsh reaction conditions 6‐8 . A series of technologies have been developed to convert CH 4 into higher‐value molecules, including the traditional steam/dry reforming, oxidative/non‐oxidative coupling and partial oxidation of CH 4 9‐11 and recently developed thermos‐photo hybrid processes 12‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of using different oxidants have been studied in several investigations. For instance, Dasireddy et al [68] studied the effects of oxidants (H 2 O, N 2 O, and O 2 ) on methane oxidation to methanol over the FePO 4 catalyst. They found that FePO 4 can actively convert methane to methanol using O 2 and N 2 O oxidants.…”
Section: Introductionmentioning
confidence: 99%